Penentuan Dosis Optimum Pemupukan N, P, dan K pada Sorgum (Sorghum bicolor [L.] Moench) - Ratna Suminar; . Suwarto; Heni Purnamawati (Jurnal Ilmu Pertanian Indonesia, 2017)
Development of sorghum processing industries is essential in expanding sorghum market as wells as it’s an economic value. Fertilizer is needed in planting. Nitrogen, phosphorus, and potassium availabilities are the most limiting factors for maximum growth and yield. Sorghum (Numbu Variety) was planted to evaluate the maximum and optimum rates of N, P, and K fertilizers. The research was conducted in Cikarawang field, Darmaga, Bogor from MarchJuly 2015 with multi-nutrient response method. Each experiment evaluated different rates of N, P, and K fertilizer with randomized complete block design and three replications. The fertilizer rates were 0, 50, 100, 150, and 200% of recommendation rate (100% N = 120 kg N ha-1, 100% P = 36 kg P2O5 ha-1, and 100% K = 90 kg K2O ha-1). The result showed relative yields of sorghum increased quadratically based on y = -0,0015x2 + 0,4011x + 67,571 for N, y = -0,0012x2 + 0,2917x + 78,457 for P2O5, and y = -0,001x2 + 0,2777x + 74,457 for K2O. The maximum rate for each nutrient was 160,4-43,7-124,9 kg N-P2O5-K2O ha-1. Fertilizer recommendation based on P threshold (no P) was 36,7-0,0-13,7 kg N-P2O5-K2O ha-1, K threshold (no K) was 22,0-0,0-0,0 kg N-P2O5-K2O ha-1, and no fertilizer needed on N threshold. The optimum rate fertilizer based on the yield vs. cost rule, therefore, the most economical recommendation would be 160,4-43,7-124,9 kg N-P2O5-K2O ha-1.